Extravasation of contrast medium resembling hematoma following iatrogenic vascular trauma: Case report - Anita Jagetia; Sanjay Gupta; Pankaj Sarda; Daljit Singh; Sanjiv Sinha (The Indian Journal of Neurotrauma, 2009)
The complication rate of cerebral angiography is 0.4 to 12.2% and stroke patients are at increased risk. Non-contrast CT head done for deterioration following angiographic procedures may show hyperdensity. This hyperdensity usually suggests the presence of a procedure induced hematoma. Rarely, it may be due to contrast extravasation. A high index of suspicion is needed in the latter group of patients to avoid unnecessary surgery. Two cases showing hyperdense lesions on non-contrast CT following iatrogenic vascular trauma during angiography and related procedures are presented with special emphasis on features which help to differentiate contrast extravasation from procedure induced hematoma.